2011
DOI: 10.3892/ijmm.2011.724
|View full text |Cite
|
Sign up to set email alerts
|

The sap of Acer okamotoanum decreases serum alcohol levels after acute ethanol ingestion in rats

Abstract: Abstract. In the present study, we examined whether Acer okamotoanum (A. okamotoanum) sap decreased the serum alcohol and acetaldehyde levels after acute ethanol treatment in a rat model. Male rats were orally administered 25, 50 or 100% A. okamotoanum sap 30 min prior to oral challenge with 3 ml of ethanol (15 ml/kg of a 20% ethanol solution in water), and the blood concentrations of alcohol and acetaldehyde were analyzed up to 7 h after the treatment. Pre-treatment with the sap significantly decreased the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…A previous study demonstrated that administration of isoquercitrin for five weeks inhibited hepatic inflammation and oxidative stress by suppressing transforming growth factor beta (TGF-β), signaling in the HFD-induced mice [37]. In addition, the sap of EAO reduced the hepatic oxidative stress and apoptosis in the alcohol-induced hepatic damage mouse model [45]. Therefore, our results suggest that EAO and isoquercitrin attenuate HFD-induced liver toxicity in HFD-and Aβ-induced mice.…”
Section: Discussionsupporting
confidence: 53%
“…A previous study demonstrated that administration of isoquercitrin for five weeks inhibited hepatic inflammation and oxidative stress by suppressing transforming growth factor beta (TGF-β), signaling in the HFD-induced mice [37]. In addition, the sap of EAO reduced the hepatic oxidative stress and apoptosis in the alcohol-induced hepatic damage mouse model [45]. Therefore, our results suggest that EAO and isoquercitrin attenuate HFD-induced liver toxicity in HFD-and Aβ-induced mice.…”
Section: Discussionsupporting
confidence: 53%
“…The alcohol was decomposed into acetaldehyde by ADH and, subsequently, into acetate by ALDH, and then into carbon dioxide and water by the tricarboxylic acid cycle. Thus, the severely ethanol-induced liver injury might be associated with the activities of ADH and ALDH [ 39 ]. The CYP2E1 is one of important metabolic enzymes, which catalyzes the conversion of ethanol to acetaldehyde but, at the same time, also produces high amounts of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Yoo and colleagues demonstrated that sap obtained from Acer pictum Thunb. (Acer okamotoanum) boosts alcohol metabolism in rats and protects against ethanol-induced apoptosis in hepatocytes [31]. In this study, we showed that raw tree saps from Betula pendula Roth., Alnus glutinosa Gaertn., and Carpinus betulus L. can stimulate metabolic activity in HepG2 model of human hepatocytes in vitro.…”
Section: Discussionmentioning
confidence: 74%